Kompetensi Komunikasi Pengguna Aplikasi Tinder Sebagai Media Pencari Jodoh di Masa Pandemic - Pramistiyani, Aymelia; Oktaviani, Femi (Sarjana Terapan Prodi Humas dan Komunikasi Digital Fakultas Ilmu Sosial Universitas Negeri Jakarta, 2022)
This research is based on the communication competence of Tinder application users. Tinder application as an alternative media in finding a mate during the pandemic. Communication competence or a person's ability to communicate will build a trust in an ongoing relationship, even though this communication only takes place through chat media, it does not hinder the communication undertaken. The foundation in this research is interpersonal communication, interpersonal communication is considered the most effective in changing attitudes, beliefs, opinions and behavior of the communicant. The theory used in this research is Social Penetration Theory. The method used in this research is the researcher uses a qualitative approach with the case study method, the data collection technique in this study is in-depth interviews with Tinder application users. The results of this study that the communication competence of Tinder application users can be seen from how Tinder application users manage emotions in chat rooms, determine message content in responding to chats, and build interpersonal relationships through chat media. From these findings it can be concluded that a relationship can be built from a trust. Trust in communication using Tinder arises because of communication skills in the form of expressions, responses, and personal behavior and clear interpersonal information exchange.